Evaluation of women’s perceived safety after dark using VR (Virtual Reality) technology - Kazemidemneh, Maryam (My University, 2025)
The development of public lighting has changed the appearance of cities and opened opportunities to extend daily activities into the night. The quality and quantity of lighting has a significant impact on people's participation in nighttime activities, and in particular, their sense of safety and security in public areas such as streets and sidewalks. This research looks at how lighting design can increase the perception of safety for women. This study investigated the effect of certain types of lighting design on women’s perceived safety after dark in an outdoor urban environment, using virtual reality (VR) technology. Eight distinct lighting scenarios were created, which included variations in lighting height (bollard and pole), color temperature (warm and cool), and façade lighting (upper and lower). A within-subject experimental design was employed, where each participant experienced all lighting scenarios. The experiment was divided into two separate 2x2 factorial design studies. The first experiment explored the effect of color temperature and lighting height on perceived safety, with participants experiencing four scenarios that combined warm and cool color temperatures with bollard and pole lighting. The second experiment introduced upper and lower façade lighting and its effect when paired with bollard and pole lighting. The simulated site was a representation of a residential street in a medium-sized city in the United States. Fifty female volunteers were recruited to participate in the study. Each participant wore a VR headset and after virtually walking through the eight lighting scenarios, they rated their perceived safety using a Likert scale. After collecting the data, statistical analyses, including ANOVA and post-hoc tests, were performed to assess the main and interaction effects of lighting type, color temperature, and façade lighting on women’s perceived safety. The main effects examined how each factor—color temperature, lighting height, and façade lighting—individually influenced perceived safety. The interaction effects, on the other hand, examined whether the combination of these factors produced a different impact on perceived safety, indicating how the effect of one factor might change depending on the level of another. In the first experiment, the results indicated that participants felt safer in scenarios with bollard lighting, and combining bollard lighting with pole lighting significantly enhanced their perceived safety. However, t-test calculations showed that the effect of color temperature on perceived safety was not statistically significant, and the ANOVA test results revealed no significant interaction effect between lighting height and color temperature, indicating that the influence of lighting height on perceived safety was not dependent on the color temperature. The second experiment showed that lighting height and façade lighting had a significant main effect on perceived safety. Façade lighting on the lower part of buildings made participants feel safer compared to upper façade lighting, and similar to the first experiment, bollard lighting when combined with pole lighting, significantly increased perceived safety. However, the ANOVA test did not reveal any significant interaction effect between lighting height and façade lighting, indicating that the influence of lighting height on perceived safety was independent of the type of façade lighting, and vice versa. The results of this study provide valuable insights into the effectiveness of various lighting design strategies for enhancing women’s perceived safety in urban environments after dark. Policymakers, including organizations such as the Illuminating Engineering Society (IES), the International Dark-Sky Association (IDA), the U.S. Department of Energy (DOE), transportation planners, and public works staff can utilize this information to develop regulations and guidelines to promote effective lighting solutions that will enhance perceived safety, which can lead to increased walkability in urban areas, contributing to the vibrancy of public spaces. In addition to policymakers and organizations, the findings of this study are equally beneficial for architects, urban designers, and lighting professionals. These practitioners can integrate insights into their design processes to create urban spaces that prioritize safety. Architects, in particular, can apply these results to design buildings with exterior elements that thoughtfully incorporate lighting, enhancing both the architectural aesthetic and the overall sense of safety in the surrounding environment. This research shows that thoughtful lighting design can significantly influence human health and well-being by fostering a sense of security that encourages individuals to engage in outdoor activities, ultimately creating healthier, more active communities.
Keywords: Lighting design; Virtual Reality; Perception of safety